Major primary bile salts repress Salmonella enterica serovar Typhimurium invasiveness partly via the efflux regulatory locus ramRA - Giraud, Etienne; Baucheron, Sylvie; Foubert, Isabelle; Doublet, Benoît; Nishino, Kunihiko; Cloeckaert, Axel (Frontiers in Microbiology, 2024)
Bile represses Salmonella enterica serovar Typhimurium (S. Typhimurium) intestinal cell invasion, but it remains unclear which bile components and mechanisms are implicated. Previous studies reported that bile inhibits the RamR binding to the ramA promoter, resulting in ramA increased transcription, and that ramA overexpression is associated to decreased expression of type III secretion system 1 (TTSS-1) invasion genes and to impaired intestinal cell invasiveness in S. Typhimurium. In this study, we assessed the possible involvement of the ramRA multidrug efflux regulatory locus and individual bile salts in the bile-mediated repression of S. Typhimurium invasion, using Caco-2 intestinal epithelial cells and S. Typhimurium strain ATCC 14028s. Our results indicate that (i) major primary bile salts, chenodeoxycholate and its conjugated-derivative salts, cholate, and deoxycholate, activate ramA transcription in a RamR-dependent manner, and (ii) it results in repression of hilA, encoding the master activator of TTSS-1 genes, and as a consequence in the repression of cellular invasiveness. On the other hand, crude ox bile extract and cholate were also shown to repress the transcription of hilA independently of RamR, and to inhibit cell invasion independently of ramRA. Altogether, these data suggest that bile-mediated repression of S. Typhimurium invasion occurs through pleiotropic effects involving partly ramRA, as well as other unknown regulatory pathways. Bile components other than the bile salts used in this study might also participate in this phenomenon.